Summer solstice optimizes the thermal growing season - Victor Van der Meersch; E. M. Wolkovich (Proceedings of the National Academy of Sciences, 2025)
Multiple studies have recently proposed the summer solstice as a universal cue for major plant physiological processes. While this would have strong implications for fundamental plant biology and climate change forecasting, we currently have no clear mechanisms to explain the emergence and importance of solstice as a cue. Here, we analyze temperature accumulation patterns in relation to the summer solstice across Europe and North America—in past, historical, and projected future climates. We show that, on average, the summer solstice coincides with a thermal optimum during the growing season. However, we also find significant local variation in the timing of this optimum across different climates—suggesting the potential of alternative cues.